Dampak Pengguna Gadget Tehadap Kesehatan Mental Remaja - Eribica Ulta Olevidia; M. Fahli Zatrahadi; Miftahuddin Miftahuddin (AflahConsilia : Jurnal Bimbingan dan Konseling, 2026)
Excessive gadget use among adolescents is a serious concern. This study aims to explain adolescents' subjective experiences regarding how gadget use affects their mental health. The study used a qualitative, descriptive phenomenological approach, and data were collected through a Google form containing open-ended questions from adolescents aged 14 to 18 who use devices for at least 4 to 6 hours daily. The Colaizzi method was used to analyze the data. The results showed that excessive gadget use impacts social anxiety, sleep disturbances, social isolation, digital behavioral dependency, and decreased desire to learn. In adolescents, social media exposure leads to social comparison, which leads to feelings of inferiority and depression.